KONSTRUKSI GENDER DALAM PERKAWINAN "NYAKAK" DAN "SEMANDA" DI MASYARAKAT ADAT SAIBATIN LAMPUNG - Dasrun Hidayat (Lingkar Studi Komunikasi (LISKI), 2016)
This study focuses on the marital status Nyakak construction and Semanda in customary marriage Saibatin society. Construction of the meaning of the marital status through a gender perspective. Saibatin recognize three types of marital status; (1) marriage Nyakak, (2) the marriage Semanda, (3) and marriage Kings. The study used a qualitative approach to the constructivist paradigm and methods of phenomenology. Saibatin informant indigenous peoples who undergo marital status Semanda and Nyakak Sukabanjar Lampung village. The study states that indigenous peoples Saibatin Lampung, more familiar forms of marital status Nyakak and Semanda. Marital status used as one of the conditions determining customary title or Juluk Adok the bride and groom. Saibatin society, explicitly recognize patriarchal lines or following the path of man, so that after marriage the wife came home with the husband's family or customary terms Saibatin namely Nyakak. While the application of marriage Semanda, know matrilineal system, after marriage the husband follows the lines and kinship status wife. All related roles and responsibilities of the material as well as customs automatically switch family wife. Nyakak marriage and Semanda occur due to several factors such as economic status, parents have many children, all children consisting of all female or all male, child, first child and for not getting permission from parents. Marital status Kings today become an alternative for indigenous communities Saibatin. They decided this as a gesture of rights and the same responsibilities, so that they do not wish to be bound by or among the family of marital status. Marriage Kings is rated as a solution in the middle of gender dominiasi between family men and women.